Stakeholders’ Perceptions towards Land Restoration and Its Impacts on Ecosystem Services: A Case Study in the Chinese Loess Plateau - Hao Chen; Luuk Fleskens; Simon W. Moolenaar; Coen J. Ritsema; Fei Wang (Land, 2022)
To combat land degradation and deterioration issues, the Grain to Green project (GGP) was implemented on the Chinese Loess Plateau in 1999 and substantially altered the land cover by converting slope farmland into forest and grassland. To effectively achieve sustainable land restoration management and avoid stakeholder conflicts, this study aimed to understand how local stakeholders perceived the current land restoration process and expectations for future land restoration policy, as well as how stakeholders assessed the GGP impacts on local ecosystem service changes. We investigated the perspectives of 150 stakeholders representing five stakeholder groups including farmers, governmental officers, citizens, tourism operators and forestry practitioners using questionnaires administered in 2021 in the Yan’an area of the Chinese Loess Plateau. The survey results indicated a 72% support rate of stakeholders for the current GGP, with government officers reporting the highest value and tourism practitioners reporting the lowest. The support rate for future land restoration decreased to 51%. While majority of the stakeholders considered that the GGP had stimulated regulation and cultural ecosystem services, they also perceived negative impacts on grain production, livestock production, water yield and water quantity. Factors influencing farmers’ decision-making on recultivating the restored forest in the future were found to be economically driven. We recommend policy makers to improve the compensation standards and duration for farmers and increase the diversity of restoration tree species, and the involvement of participatory processes is suggested for future land restoration policy-making.